Perilaku kesehatan sebagai faktor risiko masalah kesehatan gigi dan mulut anak - Elisanditya, Amabelle; Hapsari Andayani, Lia; Gani Soulisa, Abdul (Jurnal Kedokteran Gigi Terpadu, 2025)
According to data from Riset Kesehatan Dasar 2018 (Riskesdas), 88.8% of Indonesians had dental cavities. The Decayed (D) component contributed the highest number, 4.5, to the average Decayed, Missing, and Filled Teeth (DMFT) score of 7.1. This demonstrates how widespread oral health and dental issues are in Indonesia. The bulk of dental and oral health issues affect children, who make up half of the world's population. According to data, the percentage of caries in children aged 5 to 9 years was 92.6%, whereas the percentage in children aged 10 to 14 years was 73.4%. This figure illustrates that dental health problems in children are very common and require greater attention. Various factors contribute to the high prevalence of dental and oral problems among children. These factors include individual bad habits, unhealthy diet as well as lack of parental awareness and attention in maintaining children's dental hygiene. Sweet foods and drinks containing excessive sugar, coupled with irregular tooth brushing habits, are one of the main causes of dental caries in children. Therefore, prevention efforts through education about the importance of maintaining oral hygiene and healthy eating patterns are very necessary to reduce dental and oral health problems among children.